2021
DOI: 10.1007/s11655-021-3341-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electro-acupuncture on Vasomotor Symptoms in Rats with Acute Cerebral Infarction Based on Phosphatidylinositol System

Abstract: Objective To investigate the effect of electro-acupuncture (EA) on vasomotor symptoms in rats with acute cerebral infarction, by observing the changes in the expression of factors related to the phosphatidylinositol (PI) system. Methods Forty-two Wistar rats were randomly divided into 3 groups by a random number table: the control group ( n =6), the model group ( n =18) and the EA group ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…Moreover, acupuncture therapy promotes synaptic plasticity and facilitates nerve repair through different ways (Qing et al, 2016 ). According to some studies, acupuncture has also been shown to be effective in regulating vasomotor contraction and preventing cerebral vasospasm (Ko et al, 2013 ; Li et al, 2022 ). However, it is unfortunate that the case report falls under Level IIIb of the evidence scale developed by the Center for Evidence-based Medicine at the University of Oxford and there are no systematic reviews or randomized controlled trials (RCTs) reports on acupuncture treatment for nerve sequelae resulting from electric injuries as far as.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, acupuncture therapy promotes synaptic plasticity and facilitates nerve repair through different ways (Qing et al, 2016 ). According to some studies, acupuncture has also been shown to be effective in regulating vasomotor contraction and preventing cerebral vasospasm (Ko et al, 2013 ; Li et al, 2022 ). However, it is unfortunate that the case report falls under Level IIIb of the evidence scale developed by the Center for Evidence-based Medicine at the University of Oxford and there are no systematic reviews or randomized controlled trials (RCTs) reports on acupuncture treatment for nerve sequelae resulting from electric injuries as far as.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatidylinositol is involved in the regulation of multiple signalling pathways in skin cells, including cell proliferation, apoptosis, and differentiation. 27,28 Li J et al 29 have This may be a metabolic mechanism of action of electroacupuncture to promote wound repair.…”
Section: Discussionmentioning
confidence: 99%
“…EA was found to reverse the upregulation of the IP3 signal transduction pathway via inhibiting Ang II binding to AT1R, which improved the blood supply of ischemic areas and had a beneficial effect on cerebral ischemia ( 34 ). Likewise, the other study found that EA effectively decreased the over-expression of DAG, IP3, and calmodulin in rats with acute cerebral infarction, improved cerebral autonomy movement, and alleviated cerebral vascular spasm ( 35 ).…”
Section: Acupuncture Mechanisms On Cerebral Perfusion In Ischemic Strokementioning
confidence: 92%